Suppression of Human Tenon Fibroblast Cell Proliferation by Lentivirus-Mediated VEGF Small Hairpin RNA - Zhongqiu Li; Wen Hua; Xuedong Li; Wei Wang (Journal of Ophthalmology)
Purpose. The functions of vascular endothelial growth factor (VEGF) in scar formation after trabeculectomy were investigated in a human Tenon fibroblast cell line from glaucoma patients using lentivirus-mediated VEGF shRNA. Methods. Human Tenon fibroblast (HTF) cells were isolated from scar tissue of glaucoma patients during secondary surgery. Lentivirus-VEGF-shRNA was constructed and transfected into HTF cells. Subsequently, VEGF mRNA and protein expression were analyzed using quantitative RT-PCR and western blotting, respectively, and the effects of VEGF knockdown were analyzed. The inhibition of HTF proliferation was monitored according to total cell numbers using ScanArray. Results. Both mRNA and protein levels of VEGF were reduced by lentivirus-mediated VEGF-shRNA, and proliferation of HTF cells was inhibited. Conclusions. Primary cultures of human Tenon fibroblast (HTF) were established, and proliferation was decreased following inhibition of VEGF. VEGF may be a suitable therapeutic target for reducing scar tissue formation in glaucoma patients after filtration surgery.